Praktik Jual Beli Meubel dengan Sistem Pesanan di Usaha Meubel Pak No Kelurahan Rano dalam Perspektif Hukum Ekonomi Syariah - Nelly Agustriani; Nilfatri Nilfatri; Triyana Wulandari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study was conducted to determine how the practice of buying and selling furniture with a custom system in the Pak No furniture business in Rano Village and how the perspective of Sharia Economic Law on the practice of buying and selling furniture with a custom system in the Pak No furniture business in Rano Village. This research is included in the type of qualitative research and uses an empirical juridical approach. In practice, the Pak No furniture business implements a custom system of buying and selling with installments and then pays off after the goods are finished. Viewed from the perspective of Sharia Economic Law, the practice of buying and selling orders in the Pak No furniture business is included in the istishna' contract. Then a problem arose in the practice of buying and selling in the Pak No furniture business, one of which is the buyer who does not fulfill the agreement. The buyer does not take the ordered goods when they are finished, so it can break the istishna' contract. According to the Compilation of Sharia Economic Law, the above problem is included in the causes of the cancellation of the istishna' contract.